The effect of using cooperative learning model type of examples non examples and motivation toward student learning outcomes - Aulia Rahuma; Azwar Ananda (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2018)
This research aims to find out : (1) the differences outcomes learning of the social student subject between student taught by using example non example model and student taught by using convensional model (2) the differences outcomes learning of the social student subject between student taught by using example non example model with convensional models by looking from leaarning motivation. (3) the influence of interaction between example non example models with convensional models. This study is an experimental research (qasi-experiment) with a 2x2 factorial design. Analysis data in this research was use anava statistical test. Research finding suggest that : (1) there are differences outcomes learning of the social student subject between student taught by using example non example model and student taught by using convensional models (2) the students which have high motivation in learning that given by example non example models socialstudent subject are higher than convensional models students. (3) the students which have low motivation in learning outcomes learning of the social student are higher given by using conventional models than use example non example models. (4) there is an influence of interaction between example non example models with convensional models with learning motivation ( high – low) on the result of social student subject.